Evaluation of the Impacts of Pesticides Exposure in Different Durations on the Neural System and Antioxidants in Iraqi Farmers - Abdulsalam, Haneen; Azeez, Maan Abdul; Jouda, Jamela (Iraqi Journal of Science, 2024)
The objective of this research was to investigate the effects of pesticides in different durations on some neurotransmitters and oxidative parameters compared to controls. A total of 120 male farmers participated in this study, 30 not exposed to pesticides served as control group and 90 exposed to pesticides and were split into two groups based on their exposure durations (˂5 & ≥5 years) and three age-groups (˂20, 20-40 and ≥41 years). Blood was collected to determine acetylcholinesterase (ACHE), serotonin (5-TH), dopamine (DA), reactive oxygen species (ROS), total antioxidant capacity (TAC) and malondialdehyde (MDA) levels using ELISA kits. The results of ACHE, serotonin, dopamine and TAC levels increased, whereas MDA and ROS levels decreased among farmers exposed to the pesticides. According to the exposure duration and farmers age, only 5-TH, DA and TAC levels were affected. It can be concluded that pesticides exposure may have an acute effect on acetylcholine and a chronic effect on the serotonin and dopamine via change in the antioxidant system which may play an important role in the neural diseases.